AKTIVITAS KOMUNIKASI PEMASARAN UMKM KAPULAJANG DALAM MEMBANGUN BRAND AWARENESS MELALUI MEDIA SOSIAL INSTAGRAM @Kapulajangofficial - Bryanfika Siti Cahyani Murdani; Herning Suryo; Estu Widiyowati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study was motivated by the phenomenon of increasing use of social media, particularly Instagram, as a means of marketing communication by small and medium enterprises (SMEs). Kapulajang SMEs, as producers of cardamom green tea, face challenges in building brand awareness amid fierce competition and the relative newness of their business. The purpose of this study is to analyze the marketing communication activities carried out by Kapulajang SME in building brand awareness through Instagram @kapulajangofficial. This study uses the theoretical basis of marketing communication, marketing mix, social media theory (Kaplan & Haenlein, 2010), and the concept of brand awareness (Aaker and Keller). The research method used was qualitative with a descriptive approach through a single case study. The research subjects were the Kapulajang MSME team and its consumers. Data collection techniques were carried out through semi-structured interviews, digital and field documentation studies, and analyzed using the Miles and Huberman interactive model. Data validity was tested through source triangulation. The results of the study show that Kapulajang MSMEs have successfully achieved Brand Acceptability through the implementation of a consistent marketing communication mix. The advertising strategy was carried out by utilizing Instagram features such as Reels, Posts, Stories, Highlights, and Direct Messages, combined with a green brand visual identity and mental health-themed content. Sales promotions were carried out incidentally, such as seasonal discounts and new packaging launches. Public relations activities were realized through narratives on the empowerment of kapulaga farmers and mental health issues, while direct marketing was carried out through active interaction with consumers via Instagram and WhatsApp. All of these activities built strong brand associations and made it easier for consumers to recognize and access Kapulajang products. Keywords: Marketing Communication, Brand Awareness, Instagram, Social Media, Kapulajang SMEs.